Aziz Mahmud Hüdâyî'nin hayatı ve bestelenmiş eserleri - Cevlek, Enes (My University, 2021)
Tarîkat mensûbu mûsikîşinasların yapmış oldukları bestelerin tekkelerde, zikir meclislerinde ve sâir mekanlarda icra edilmiş ve edilmekte olmasının, Türk Din Mûsikîmizin nesilden nesile aktarılmasında, inkişafında ve tekâmülünde inkar edilemeyecek bir rolü olduğu düşünülmektedir.Dîvanların, bestekârlarımıza hatırı sayılır derecede güfte kaynaklığı yaptığı söylenebilir.Bu çalışmamızda Celvetiyye Tarîkatı Şeyhi, dîvan sahibi ve bestekâr olan Aziz Mahmud Hüdâyî‟nin hayatı hakkında (kaynaklardan ulaşılabildiği kadarıyla) malumat verilmiştir. Şiirlerine yapılan besteler derlenmiş, yeniden notaya alınmış, güfteleri dîvandan teyid edilmiştir. Nihâî olarak da elde edilebilen 195 bestenin, sırasıyla güfte-makâm-bestekâr-usûl-form analizleri yapılarak mûsikîmizin istifâdesine arz etmek hedeflenmiştir.

It is thought that the compositions made by the music members of the order have been performed and are being performed in dervish lodges, dhikr assemblies and other places, and it has an undeniable role in the transmission, development and evolution of our Turkish Religious Music from generation to generation.It can be said that Divans have been a considerable source of lyrics for our composers.In this study, information is given about the life of Aziz Mahmud Hüdâyî, who was the sheikh of the Celvetiyye Sect, the owner of the divan and the composer (as far as can be reached from the sources). The compositions for his poems were compiled, re-noted, and their lyrics were confirmed from the divan. It is aimed to present the 195 compositions, which can also be obtained in the final, for the benefit of our music by analyzing lyrics-maqam-composer-method-form respectively.
Keywords: Aziz Mahmud Hüdâyî; Celvetiyye; Divan; Dîvan; Mahmut Hüdayi, 1543 or 4-1628; Sufi music; Tasavvuf müziği; Turkish Religious Music; Türk Din Mûsikîsi